Self-efficacy beliefs in managing positive emotions: Associations with positive affect, negative affect, and life satisfaction across gender and ages - Caprara, Mariagiovanna; Gerbino, Maria; Mebane, Minou Ella; Ramirez-Uclés, Isabel M. (Frontiers in Human Neuroscience, 2022)
Two studies were carried out on a Spanish population to explore the extent to which different self-efficacy beliefs in managing positive emotions are associated with common indicators of well-being, such as positive and negative affect or life satisfaction. The first study was conducted on 483 participants and attested to the factorial structure of three different self-efficacy beliefs: (a) perceived self-efficacy in expressing positive emotions; (b) perceived self-efficacy in retrieving memories of positive emotional experiences; and (c) perceived self-efficacy in using humor. The second study was carried out on 1087 individuals between 19 and 80 years of age, and it provided evidence of the factorial invariance of the scales across age and gender. Furthermore, this latter study showed the association of Self-efficacy in Managing Positive Affect (SEMPA) with high chronic positive and low negative affect, and with high life satisfaction, controlling for gender and age. In younger participants, stronger associations were found between perceived self-efficacy in using humor and life satisfaction compared to older subjects. These findings may guide the design of interventions aimed at enhancing the potential benefits that could be drawn from the proper management of positive emotions.